Modification of the turbulence properties at the bow shock: statistical results - Rakhmanova, Liudmila; Khokhlachev, Alexander; Riazantseva, Maria; Yermolaev, Yuri; Zastenker, Georgy (Frontiers in Astronomy and Space Sciences, 2024)
Turbulent solar wind is known to be a main driver of the processes inside the magnetosphere, including geomagnetic storms and substorms. Experimental studies of the last decade demonstrate additional ways of interplanetary plasma transport to the magnetosphere, including small-scale processes in the magnetosphere boundary layers. This fact implies that properties of the solar wind turbulence can affect the geomagnetic activity. However, in front of the magnetosphere are a bow shock and a magnetosheath region which contribute to the changes in the properties of the solar wind turbulence and may result in destructions of the association between solar wind turbulence and the magnetosphere. The present study provides the statistics of two-point simultaneous measurements of the turbulence properties in the solar wind and the magnetosheath based on Wind and THEMIS spacecraft data. Changes in the turbulence properties are analyzed for different background conditions. Solar wind bulk speed and temperature are shown to be the main factors that influence the modification of turbulence at the quasi-perpendicular bow shock at frequencies higher than the break frequency (ion transition range). Inside the magnetosheath, significant steepening of spectra occurs with an increase in temperature anisotropy without a connection to the upstream spectrum scaling that underlines the crucial role of the instabilities in turbulence properties behind the bow shock.